Hypoxia-induced responses by endothelial colony-forming cells are modulated by placental growth factor. Issue 1 (December 2016) - Hookham, Michelle; Ali, Imran; O'Neill, Christina; Hackett, Emer; Lambe, Melanie; Schmidt, Tina; Medina, Reinhold; Chamney, Sara; Rao, Bharathi; McLoone, Eibhlin; Sweet, David; Stitt, Alan; et al.
Abstract Background Endothelial colony-forming cells (ECFCs), also termed late outgrowth endothelial cells, are a well-defined circulating endothelial progenitor cell type with an established role in vascular repair. ECFCs have clear potential for cell therapy to treat ischaemic disease, although the precise mechanism(s) underlying their response to hypoxia remains ill-defined. Methods In this study, we isolated ECFCs from umbilical cord blood and cultured them on collagen. We defined the response of ECFCs to 1% O2 exposure at acute and chronic time points. Results In response to low oxygen, changes in ECFC cell shape, proliferation, size and cytoskeleton phenotype were detected. An increase in the number of senescent ECFCs also occurred as a result of long-term culture in 1% O2 . Low oxygen exposure altered ECFC migration and tube formation in Matrigel®. Increases in angiogenic factors secreted from ECFCs exposed to hypoxia were also detected, in particular, after treatment with placental growth factor (PlGF). Exposure of cells to agents that stabilise hypoxia-inducible factors such as dimethyloxalylglycine (DMOG) also increased PlGF levels. Conditioned medium from both hypoxia-treated and DMOG-treated cells inhibited ECFC tube formation. This effect was reversed by the addition of PlGF neutralising antibody to the conditioned medium, confirming the direct role of PlGF in this effect. Conclusions This study deepens our understanding of the response of ECFCs to hypoxia and also identifies a novel and important role for PlGF in regulating the vasculogenic potential of ECFCs.